WHAT HINDERS TEACHERS OF EFL TO PERFORM PROFESSIONALLY IN THE CLASSROOM - Muhammad Amin (Universitas Muhammadiyah Ponorogo, 2016)
This paper has tried to elaborate several factors which may inhibit a teacher of EFL to perform professionally in the classroom. Although the list provided here cannot be claimed comprehensive, as there are surely still other factors at play, at least it has raised some very important issues relating to one of the key components in education. Quality of teachers should be ensured and of priority if to enhance and maintain quality of education and all related stakeholders of education should play a role in supporting teachers to perform professionally in the classroom. One of the ways is to prevent those possible causes of professional teaching performance to exist among teachers.